To Know whether all know identities

Algebra Level 2

True or False ?

( x y ) 3 = x 3 y 3 + 3 x y ( x y . ) (x-y)^3=x^3-y^3+3xy(x-y.)

Cannot determine False True

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Replace x 3 y 3 = ( x y ) 3 + 3 x y ( x y ) x^{3}-y^{3} = (x-y)^{3}+3xy(x-y)

( x y ) 3 = [ ( x y ) 3 + 3 x y ( x y ) ] + 3 x y ( x y ) = ( x y ) 3 + 6 x y ( x y ) \Rightarrow (x-y)^{3}=[(x-y)^{3}+ 3xy(x-y)] +3xy(x-y) =(x-y)^{3}+ 6xy(x-y)

Therefore, ( x y ) 3 x 3 y 3 + 3 a b ( a b ) (x-y)^{3} \not= x^{3}-y^{3}+3ab(a-b) , which is F a l s e \boxed{False}

Vishwash Kumar
Nov 2, 2016

Yeah , It can be true in case that x becomes equal to y . You should have provided it x is not equal to y

Arulx Z
Aug 17, 2015

It must be

x 3 y 3 3 x y ( x y ) { x }^{ 3 }-{ y }^{ 3 }-3xy(x-y)

Azadali Jivani
Aug 14, 2015

(x-Y)^3 = X^3 - Y^3 - 3X^2 + XY^2 (Ans.)

Once check your solution properly.

Rama Devi - 5 years, 10 months ago

Log in to reply

Did this question was inspired by my question ? Isn't it .

Anish Harsha - 5 years, 10 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...